Volume 5: Turbo Expo 2004, Parts a and B 2004
DOI: 10.1115/gt2004-53765
|View full text |Cite
|
Sign up to set email alerts
|

Inlet Air Cooling Methods for Gas Turbine Based Power Plants

Abstract: Power generation from gas turbines is penalised by a substantial power output loss with increased ambient temperature. By cooling down the gas turbine intake air, the power output penalty can be mitigated. The purpose of this paper is to review the state of the art in applications for reducing the gas turbine intake air temperature and examine the merits from integration of the different air-cooling methods in gas turbine based power plants. Three different intake air-cooling methods (evaporative cooling, refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Kakaras [3] reported that the efficiency of the gas turbine is strongly related to the ambient air temperature. According to the gas turbine type, the output power is reduced by 5 to 10% of the rated power at 288 K according to the ISO standard for each increase of 10 K in the temperature of the ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…Kakaras [3] reported that the efficiency of the gas turbine is strongly related to the ambient air temperature. According to the gas turbine type, the output power is reduced by 5 to 10% of the rated power at 288 K according to the ISO standard for each increase of 10 K in the temperature of the ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the gas turbine type, power output is reduced by a percentage between 5 to 10 percent, of the ISO-rated power output (15oC), for every 10 oC increase in ambient air temperature. At the same time, the specific heat consumption increases by 1.5 to 4 percent (Kakaras, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…[10] work done shows that an increase of 1C 0 in the compressor air inlet temperature decreases the gas turbine power output by 1% . The effect of integration of the inlet air-cooling systems was presented in [11], for two selected combined cycle power plants and two gas turbine plants. The calculation were performed on a yearly basis of operation and the timevarying climatic conditions were taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%